The absence of vision impacts attentional focus effects during a balancing task - Becker, K. A.; McNamara, S. W. (Research Quarterly for Exercise and Sport, 2023)
Purpose: Recent work involving reaching and aiming tasks provides evidence that an internal focus results in less error than an external focus when visual information is removed. The purpose of this study was to extend these findings by determining how an internal and external focus impact motor performance during a balancing task for adults with and without visual occlusion. Method: Thirty-two undergraduate students were randomly assigned to perform the task with or without visual occlusion. Participants balanced on a stability platform during four familiarization trials, three internal focus trials, and three external focus trials. Results: A significant Focus x Vision interaction indicated the group without visual occlusion had significantly lower root mean square error (RMSE) with an external focus, whereas the group with visual occlusion had lower RMSE with an internal focus. Conclusions: These findings indicate that for tasks that rely on online sensory feedback, such as balancing, the optimal attentional focus may be dependent on the dominant type of sensory feedback that is available.